1993
DOI: 10.1017/s0033822200064948
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotopic Composition of Deep Carbon Gases in an Ombrogenous Peatland, Northwestern Ontario, Canada

Abstract: ABSTRACT. Radiocarbon dating and carbon isotope analyses of deep peat and gases in a small ombrogenous peatland in northwestern Ontario reveals the presence of old gases at depth that are 1000-2000 yr younger than the enclosing peat.We suggest that the most likely explanation to account for this age discrepancy is the downward movement by advection of younger dissolved organic carbon for use by fermentation and methanogens bacteria. This study identifies a potentially large supply of old carbon gases in peatla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 21 publications
8
45
1
Order By: Relevance
“…Current research efforts focus on process-based modeling which includes the in¯uence of vegetation on CH 4 emission (Cao et al, 1996;Walter and Heimann, 2000). Radiocarbon measurements of CH 4 suggest that methane is produced primarily from recently-®xed carbon (Wahlen et al, 1989;Martens et al, 1992;Aravena et al, 1993;Chanton et al, 1995). Observed correlations between net ecosystem productivity (NEP) and CH 4 emission (Clymo and Reddaway, 1971;Svensson, 1983;Sebacher et al, 1986;Aselmann and Crutzen, 1989;Moore and Knowles, 1990;Whiting and Chanton, 1993;Klinger et al, 1994;Waddington et al, 1996) suggest that recent plant photosynthates may be an important source of carbon for CH 4 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Current research efforts focus on process-based modeling which includes the in¯uence of vegetation on CH 4 emission (Cao et al, 1996;Walter and Heimann, 2000). Radiocarbon measurements of CH 4 suggest that methane is produced primarily from recently-®xed carbon (Wahlen et al, 1989;Martens et al, 1992;Aravena et al, 1993;Chanton et al, 1995). Observed correlations between net ecosystem productivity (NEP) and CH 4 emission (Clymo and Reddaway, 1971;Svensson, 1983;Sebacher et al, 1986;Aselmann and Crutzen, 1989;Moore and Knowles, 1990;Whiting and Chanton, 1993;Klinger et al, 1994;Waddington et al, 1996) suggest that recent plant photosynthates may be an important source of carbon for CH 4 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, dissolved CO 2 has consistently been 52 found to be younger than the surrounding peat. For example, in Canadian boreal peatlands 53 Aravena et al (1993) and Charman et al (1994) found peat CO 2 to be between 500 and 2000 54 years younger than the adjacent peat. Another study performed in an oceanic peatland in south-55 west England (Charman et al, 1999) reported that peat CO 2 was younger than the surrounding 56 peat by between ~ 800 and 1500 years.…”
mentioning
confidence: 99%
“…As mentioned before, higher concentrations of dissolved CH 4 were measured at the approximate depth of the esker crest, suggesting that the methanogenesis rates are higher in the vicinity of the esker crest. Younger radiocarbon dates of dissolved organic carbon in deep peat indicate downward transport of labile carbon in other studies (Aravena et al, 1993;Charman et al, 1994;Chanton et al, 1995;Chasar et al, 2000). Computer simulations have also shown permeable mineral lenses to create a downward transport effect in peatlands (e.g., Reeve et al, 2009).…”
Section: Hydrologic Datamentioning
confidence: 67%
“…CH 4 in deep peat has been shown to be radiocarbon enriched compared to the surrounding peat, suggesting anaerobic respiration that is supported by a downward transport of younger dissolved organic carbon (Aravena et al, 1993;Charman et al, 1994;Chanton et al, 1995). estimated that CH 4 in pore waters contained as much as 25 % modern carbon at 2.5 m depths.…”
Section: Methane Production and Consumptionmentioning
confidence: 99%